Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm trying to figure out the generating function for this power series.. I have a few ideas but can't get any result..

$$\sum_{n=2}^\infty \left(\sum_{k=1}^{n} ((n-k)(k-1)M_{k-1}) z^n\right) $$

$M(k)$ is my recursive function.. my problem is with the $(n-k)(k-1)$ part..

I was thinking that it can be extracted from the summation and it should become

$$n(n+1)(n+2)/6$$

but I'm still unable to solve this..

share|improve this question
2  
A generating function and a (formal) power series are the same thing, so it's not clear what you're asking. –  Dimitrije Kostic Nov 21 '11 at 5:37
1  
Have you tried applying convolution backwards? –  Raphael Nov 21 '11 at 6:54
1  
If you want to solve for $M_k$, you should give the original recursion in your question. –  Raphael Nov 21 '11 at 19:28

2 Answers 2

Observe the inner product is a discrete convolution, suggesting this is a product of two generating functions. Reindex $n$ by $1$ and obtain:

$$\sum_{n=2}^\infty\left(\sum_{k=1}^n(n-k)(k-1)M_{k-1}\right)z^n=\sum_{n=1}^\infty\left(\sum_{a+b=n}a\cdot(bM_b)\right)z^{n+1}$$

$$=z\left(\sum_{a=1}^\infty az^a\right)\left(\sum_{b=1}^\infty bM_bz^b\right)=z\cdot\frac{z}{(1-z)^2}\cdot\left(z\frac{d}{dz}\sum_{b=1}^\infty M_bz^b\right).$$

Now, what is it exactly that you want to accomplish here? You say $M_k$ is a recursive function but you don't tell us what the recursion it satisfies is and you likewise refer to some "it" being a given polynomial in $n$ but what is the "it" that you refer to - is it the $M_k$ or the inner sum involving $M_k$?

Also, if you meant $z^k$ instead of $z^n$ in your first equation...

share|improve this answer

$$\sum_{n\geq2} \sum_{k=1}^{n}(n-k)(k-1)M_{k-1}z^n = \sum_{n\geq1} \sum_{k=1}^{n+1}(n+1-k)(k-1)M_{k-1}z^{n+1}$$ Interchanging order of sum: $$[1 \leq n < \infty][1 \leq k \leq n+1] =[1 \leq k \leq n+1 < \infty] $$ $$ = [1 \leq k < \infty][k \leq n+1 < \infty]$$ Hence, $$ = \sum_{k\geq 1}(k-1)M_{k-1}\sum_{n+1\geq k}(n+1-k)z^{n+1-k}z^k$$ $$ = \sum_{k\geq 1}(k-1)M_{k-1}\sum_{n\geq k}(n-k)z^{n-k}z^k$$ $$=\sum_{k\geq 1}(k-1)M_{k-1}z^k \;z\sum_{n\geq k}(n-k)z^{n-k-1} $$ $$=\sum_{k\geq 1}(k-1)M_{k-1}z^{k+1} \;\frac{d}{dz}\sum_{n\geq k}z^{n-k} $$ $$=\sum_{k\geq 1}(k-1)M_{k-1}z^{k+1} \;\frac{1}{(1-z)^2} $$ $$=\frac{z^3}{(1-z)^2}\sum_{k\geq 1}(k-1)M_{k-1} z^{k-2} $$ $$=\frac{z^3}{(1-z)^2}\sum_{k\geq 1}(k-1)M_{k-1} z^{k-2} $$ $$=\frac{z^3}{(1-z)^2}\frac{d}{dz}\sum_{k\geq 1}M_{k-1} z^{k-1} $$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.